The Loyalty Equation: Leadership, Workload, and Employer Branding for Millennials - Yudit Ayu Respati; Rosidah; Rizki Pratama Johanis Paransa; Alfiy Nur Rafi; Kalvin Deni Armanda; Nurul Afikah; Bunga Noviana Simanjuntak; Zullaikha Widyasari (Departemen Pendidikan Administrasi FEB Universitas Negeri Yogyakarta & ASPAPI PUSAT, 2024)
Millennial employee loyalty has become an important issue in contemporary human resource management due to the increasing tendency of millennials to change jobs and seek better career opportunities. Previous studies have commonly treated employee loyalty as a single construct, despite the possibility that loyalty may consist of distinct attitudinal and behavioral dimensions. Therefore, this study examines the influence of authoritarian leadership, workload, and employer branding on millennial employees' attitudinal and behavioral loyalty. This study employed an explanatory quantitative design using a survey method. Data were collected from 108 millennial lecturers at a university in Yogyakarta, Indonesia, and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The findings indicate that authoritarian leadership and workload negatively affect both attitudinal and behavioral loyalty, while employer branding positively influences both dimensions of loyalty. The results suggest that millennial employees are more likely to develop emotional attachment and organizational commitment when they perceive supportive leadership, balanced workload, and positive organizational treatment. The study contributes to the employee loyalty literature by distinguishing between attitudinal and behavioral loyalty, which are often treated as a single construct in previous studies. The distinction provides a more comprehensive understanding of employee loyalty dynamics and extends the application of social exchange theory in explaining millennial workplace behavior. Practically, the findings offer insights for organizations in developing strategies to improve millennial employee retention and commitment.